The Influence of Financial Literacy, Business Networking, and Entrepreneurial Orientation on MSME Performance in Surabaya with Market Orientation as a Moderating Variable - Nurbintari, Riris; Sukoco, Agus (IJEBD (International Journal of Entrepreneurship and Business Development), 2025)
This study investigates the influence of financial literacy, business networking, and entrepreneurial orientation on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Surabaya, with market orientation as a moderating variable. A quantitative approach was employed, and data were collected through structured questionnaires distributed to 99 MSME owners and managers. Partial Least Squares Structural Equation Modeling (PLS-SEM) was applied to analyze the data. The results indicate that financial literacy and entrepreneurial orientation significantly enhance MSME performance, whereas business networking shows no significant impact. Furthermore, market orientation does not moderate the relationship between financial literacy or business networking and MSME performance. These findings highlight the importance of strengthening entrepreneurs’ financial capabilities and entrepreneurial orientation to improve MSME competitiveness and sustainability.